In silico docking and ADMET studies on clinical targets for type 2 diabetes correlated to in vitro inhibition of α-glucosidase and pancreatic α-amylase by curcumin, 18α-glycyrrhetinic acid, rosmarinic acid, and quercetin - Apostolides, Zeno (University of Pretoria, 2022)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2022.